2018
DOI: 10.1002/aocs.12032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture and Heat Treatment of Corn Germ on Oil Quality

Abstract: The changes in the quality of crude corn oil caused by moisture and two different thermal pretreatments (oven heating and steam heating) of wet-milled corn germ were evaluated and compared with those of untreated oil. Increasing the moisture content of the corn germ from 8 to 25% before oil extraction increased the acid value (AV) (3.02-4.01 mg KOH g −1 ), peroxide value (PV) (0.52-1.05 meq kg −1 ), and the red value (7.3-8.7) and decreased the content of total tocopherols by 37% and that of γ-tocopherols by 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The color intensity of the oil changed from light yellow to darkish brown as moisture content increased, this is in similar trend with palm oil and sesame oils as reported by Torres and Maestri (). However, increase in heat applications generated increase in color intensity till a certain point before darkening of color samples were physically noticed at high heat applications, an optimum oil color of 7.7 LUR was obtained at 11.7 min and 59 °C heating temperature (Figure ) which is an acceptable level (NIS, 2000), this is in tandem with reports on some edible oils (Xu, Li, Fan, Zheng, & Deng, ) and corn germ oil reported by Zheng et al ().…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The color intensity of the oil changed from light yellow to darkish brown as moisture content increased, this is in similar trend with palm oil and sesame oils as reported by Torres and Maestri (). However, increase in heat applications generated increase in color intensity till a certain point before darkening of color samples were physically noticed at high heat applications, an optimum oil color of 7.7 LUR was obtained at 11.7 min and 59 °C heating temperature (Figure ) which is an acceptable level (NIS, 2000), this is in tandem with reports on some edible oils (Xu, Li, Fan, Zheng, & Deng, ) and corn germ oil reported by Zheng et al ().…”
Section: Resultssupporting
confidence: 83%
“…The oil expression efficiency of mechanical method of oil separation is affected by the condition of the oleaginous biomaterial and other pretreatment parameters; it has an advantage of low initial and operating costs and expressed oil samples are free of hazardous chemical substances (Bamgboye & Adejumo, ; Ibrahim & Ogunwusi, ).Processing and extraction conditions affect oil characteristics, which can also be dependent on other agronomic factors like climatic conditions, soil composition, ascension, and harvesting time (Compaore et al , ; Fakayode, Ajav, & Akinoso, ; Maestri & Guzman, ; Ogunsina, Owolarafe, & Olatunde, ). Independent variables that influence the quality and quantity of vegetable oil expressed mechanically include processing parameters like heat applications (duration and temperature) (Aktas, Gerçekaslan, & Uzlaşır, ; Raba, Chambre, Copolovici, Moldovan, & Copolovici, ; Rahma, Zekhnini, El‐Alem, & Hatimi, ) and moisture content (Fakayode & Ajav, ; Pornpipat, Hattha, & Tantanawat, ; Sarah, Widyastuti, & Ningsih, ; Udoh, Olayanju, Dairo, & Alonge, ; Zheng et al , ). Literature is very scanty on the effect of variables affecting the quality (yield) and quantity (characteristics) of vegetable oil expressed mechanically from African oil bean kernels (Aremu & Ogunalde, , ).…”
Section: Introductionmentioning
confidence: 99%
“…The conditions were referred to our previous research (Li et al, 2015). Tocopherol isomers were analyzed using HPLC‐PAD with scanning from 200 to 600 nm according to a modified method (Zheng et al, 2018). The phytosterols were analyzed according to the method adopted by Zhang et al (2020), and the analysis results of tocopherol and phytosterols are shown in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Tocopherol isomers were analyzed using HPLC‐PAD with scanning from 200 to 600 nm according to a modified method (Zheng et al, 2018a). Initially, oil samples weighing 0.2 g were dissolved with 2 mL hexane, and the injection volume was 20 μL.…”
Section: Methodsmentioning
confidence: 99%